Monitoring and evaluation of intranatal facilities at community health centre level in Siddharth Nagar district - Yadav, Surbhi; Ahmad, Shamshad; Kumar, Mahendra; Yadav, S. K.; Garg, P. K.; Bahteja, Roma (International Journal Of Community Medicine And Public Health, 2018)
Background: Despite WHO and UNICEF are leaving no stone unturn to promote breastfeeding in health facilities globally, there is poor status of breastfeeding in rural India till today. in 2012, U.P had one of the poorest maternal and neonatal health outcomes in India. Assessment the implementation of practice of skin to skin contact and early initiation of breastfeeding. Methods: It was a descriptive longitudinal study. This study was carried out in CHC Khisraha and CHC Mithwal in Siddharthnagar, over a period of 3 months. All pregnant women admitted for normal delivery during data collection period and had positive outcome was our study sample. A total of 101 samples were observed and interviewed. Results: Most of the beneficiaries were from age group 20-22 years (46.5%). Pre-term delivery was high (26.7%) in present study. Only in 12% of cases radiant warmer were switched on 20-30 minutes before delivery. Only 3% of babies born were dried with pre-warmed towel/cloth. Practice of skin to skin contact was observed in 97% of cases. Only in 18.8% of cases babies followed breast crawl. All babies were given pre-lacteal feed. Only in 8.9% of cases initiation of breastfeeding was done within 30 minutes. Conclusions: Supportive supervision of staff nurses for STS contact and BF initiation is needed. Counselling and training of ASHA worker about benefits of early BF and STS contact for both mother and baby.